CHANGES IN THE CHEMICAL COMPOSITION OF THE RAT’S HUMERI UNDER THE INFLUENCE OF YELLOW TARTRAZINE STAIN - Lukyantseva, H.V.; Pastukhova, V.A.; Kovalchuk, A.I.; Dutchak, U.M. (World of Medicine and Biology, 2019)
Long-term administration of yellow tartrazine (E102) stain to sexually mature white rats at doses of 750 mg/kg and 1500 mg/kg is accompanied by a significant dose-dependent disorder in the chemical composition of bones, namely, it leads to a significant decrease in the content of organic and mineral substances, an increase in the number of hydrophilic elements with simultaneous bone tissue overhydration. The combined use of selenase, pharmacological antioxidant action corrector, with tartrazine significantly increased bone mineralization, led to an increase in the organic and mineral substances content, and also reduced the degree of bone overhydration caused by an increase in the content of sodium and potassium under the effect of E102.